Kidney transplantation in a child with Pierson syndrome. (1st November 2017) - Guler, Sanem; Cimen, Sertac; Acott, Phillip; Whelan, Kathy; Molinari, Michele
Abstract: Congenital nephrotic syndrome is commonly associated with mutations in genes that encode podocyte and slit diaphragm proteins or the structural and regulatory proteins of the GBM. These mutations lead to the formation of dysfunctional proteins, which account for the resistance of the renal manifestations to conventional treatment methods. Consequently, patients become renal replacement therapy dependent. Mutation of the LAMB2 gene is associated with Pierson syndrome, which is an autosomal recessive disorder characterized by congenital nephrotic syndrome and ocular abnormalities. In this report, a 2‐year‐old male patient who was diagnosed with Pierson syndrome is presented. He had bilateral microcoria and developmental delay in addition to nephrotic syndrome. His renal function deteriorated rapidly, and he underwent a deceased donor kidney transplantation. He showed dramatic improvement after kidney transplantation; in addition to having good renal function, he started to catch up to his peers in terms of growth. Pierson syndrome should be considered during the diagnostic investigations of children with renal manifestations and ocular abnormalities. Children with Pierson syndrome must be evaluated in terms of kidney transplantation as soon as they are diagnosed.